Detection of Pathogenic Leptospira in Sputum of Leptospirosis Patient with Pulmonary Hemorrhage. - Handayani, Farida Dwi; Novipuspitasari, Lisa; Ahmed, Ahmed; Safari, Dodi; Hidajat, Muhammad Choirul; Soebandrio, Amin; Gasem, Muhammad Hussein (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: The pathogenic Leptospira species is the causative agent of leptospirosis, an endemic zoonotic disease in Indonesia. Misdiagnosis of the disease frequently occurs, as confirmatory diagnosis confined to highly specialized laboratories. As well, the pulmonary involvement of leptospirosis with hemoptysis is scarcely reported.Case Presentation: A 49 years-old male patient was admitted to the district hospital with acute febrile illness and a history of traveling to a malaria-endemic area in Borneo, Indonesia. Based on a chest X-ray result, the patient was clinically suspected to have pulmonary tuberculosis. However, the clinical manifestations of leptospirosis i.e. conjunctival suffusion, calf pain, and oliguria were present, and later hemoptysis was also reported. A clinical diagnosis of leptospirosis with pulmonary involvement was proposed. Immunochromatographic test (ICT)-rapid test for vivax/falciparum malaria and Ziehl-Neelsen (ZN) staining of sputum for tuberculosis results were both negative. Microscopic Agglutination Test (MAT), the IgM anti-Leptospira rapid test (lateral flow assay), and PCR amplification of both conventional and real-time (qPCR) were performed using various samples (serum, urine, and sputum). The MAT of acute single serum sample and rapid test were negative. Intriguingly, the PCR showed positive results in sputum and urine samples but not in the serum sample, highlighting the usefulness of leptospiral molecular detection to confirm further diagnosis.Conclusion: Molecular detection of pathogenic Leptospira in sputum samples can be considered for confirmatory diagnosis of leptospirosis patients with pulmonary hemorrhage. Likewise, the urine sample can be used as an option in the examination of severe leptospirosis.